Early nephrology consultation can have an impact on outcome of acute kidney injury patients - Ponce, Daniela [UNESP]; Franco Zorzenon, Caroline de Pietro [UNESP]; dos Santos, Nara Yamane [UNESP]; Balbi, André Luis [UNESP] (Oxford University Press, 2011)
Background. Patients who develop acute kidney injury (AKI) in the intensive care unit (ICU) have extremely high rates of mortality and morbidity. The objectives of this study were to compare clinical and laboratory characteristics of AKI patients evaluated and not evaluated by nephrologists in ICU and generate the hypothesis of the relationship between timing of nephrology consultation and outcome.Methods. We explored associations among presence and timing of nephrology consultation with ICU stay and in-ICU mortality in 148 ICU patients with AKI at a Brazilian teaching hospital from July 2008 to May 2010. Multivariable logistic regression was used to adjust confounding and selection bias.Results. AKI incidence was 30% and 52% of these AKI patients were evaluated by nephrologists. At multivariable analysis, AKI patients evaluated by nephrologists showed higher Acute Tubular Necrosis-Index Specific Score and creatinine level, more dialysis indications, lower urine output and longer ICU stay. The mortality rate was similar to AKI patients who were not evaluated. Nephrology consultation was delayed (>= 48 h) in 62.3% (median time to consultation, 4.7 days). Lower serum creatinine levels (P - 0.009) and higher urine output (P = 0.002) were associated with delayed consultation. Delayed consultation was associated with increased ICU mortality (65.4 versus 88.2%, P < 0.001).Conclusions. In AKI, patients evaluated by nephrologists seem to be more seriously ill than those not evaluated and present similar mortality rate. The delayed nephrology consultation can be associated with increased ICU mortality.
Keywords: acute kidney injury; intensive care unit; mortality; nephrology consultation